Monatomic lead anchored activated carbon and preparation method, related product and application thereof
The preparation of single-atom lead-anchored activated carbon by spray pyrolysis method has solved the problem of insufficient cycle times and capacity of the negative electrode of lead carbon batteries in the prior art, and achieved higher cycle times and capacity.
Patent Information
- Application Number
- CN202411798039.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-14
AI Technical Summary
The prior art does not provide an activated carbon additive for single-atom lead-anchored with more cycles and higher capacity of lead-carbon batteries and a preparation process thereof.
By mixing the lead salt with disodium ethylenediaminetetraacetate aqueous solution, adding activated carbon, stirring and filtering, a precursor solution was obtained, and then spray pyrolysis and cooling was performed to obtain single-atom lead-anchored activated carbon. This method quickly produces single-atom-distributed lead-anchored activated carbon materials.
The single-atom lead-anchored activated carbon material effectively improves the cycle times and capacity of lead-carbon batteries, significantly improving the cycle life and initial capacity of the battery.
Smart Images

Figure CN119627104A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of battery materials and relates to a single-atom lead-anchored activated carbon and a preparation method thereof, related products and applications. Background Art
[0002] Lead-acid batteries have always occupied a considerable market share due to their safety, reliability, low cost and perfect recycling technology. In renewable energy storage, lead-acid batteries are highly competitive because they are not limited by volume and mass energy density. However, the inherent intermittent and volatile nature of renewable energy places strict requirements on the anti-sulfation ability of the negative electrode of lead-acid batteries. Adding carbon materials with appropriate physical and chemical properties to the negative electrode, namely lead-carbon batteries, can significantly improve the problem of short cycle life of the negative electrode in renewable energy storage.
[0003] Different from one-dimensional and two-dimensional carbon materials (carbon black, carbon fiber) that mainly provide conductivity, three-dimensional carbon materials (activated carbon, three-dimensional graphene) have multiple mechanisms of action, including catalytic lead ion reduction, double-layer capacitor buffering current, steric hindrance and conductivity. In addition, three-dimensional carbon materials overcome the problem of easy agglomeration of one-dimensional and two-dimensional carbon materials. However, while three-dimensional carbon materials significantly inhibit the sulfation of the negative electrode, their high specific surface area and low hydrogen evolution overpotential characteristics significantly accelerate the hydrogen evolution and water loss of the battery.
[0004] In addition to the corresponding carbon materials, the negative electrode additives of lead-carbon batteries also include acetylene black, sodium lignin sulfonate, humic acid, barium sulfate and other ingredients. The traditional way of adding materials is to add each additive to the lead powder and stir it. Due to the agglomeration characteristics of each additive and the huge difference in specific gravity between activated carbon and lead powder particles, the additives cannot be evenly dispersed.
[0005] Chinese invention patent CN114497544A provides an additive-loaded activated carbon composite material and its preparation and application, with activated carbon as the carrier, and the mass ratio of the additive to the activated carbon is (0.004-0.008):1. The technology proposes to pre-immerse the activated carbon material in EDTA-2Na solution and dry it to reduce the amount of hydrogen generated during the use of the battery, thereby extending the cycle life of the battery.
[0006] Chinese invention patent CN107742696A provides a method for preparing a carbon-based additive for a lead-carbon negative electrode. The lead layer on the surface of the carbon-based additive for a lead-carbon negative electrode prepared by sensitizing, activating, and chemically plating lead in a carbon material is uniformly and densely distributed, which can significantly increase the hydrogen evolution overpotential of the carbon material, inhibit the hydrogen evolution reaction of the negative electrode of the lead-acid battery, significantly inhibit the sulfation of the negative electrode of the lead-acid battery in a partial state of charge (PSoC), and extend the cycle life of the lead-acid battery.
[0007] Chinese invention patent CN108899492A provides a lead-carbon composite material, its preparation method and application, using solid lead salt, solid strong base and carbon material as raw materials, using mechanochemical method to make the raw materials react chemically under the action of mechanical force to generate lead-carbon composite material. The lead-carbon composite material obtained by the mechanochemical synthesis method provided by this technology significantly enhances the electrochemical activity of the product and the bonding strength between lead oxide and carbon material, overcomes the problem that carbon material in lead-carbon battery is easily separated from active material due to density difference, increases the initial capacity of the battery by 1.3 times, and increases the HRPSoC (high rate partial state of charge) cycle life by more than 3 times, which is of great significance to the improvement of lead-carbon battery performance.
[0008] However, the prior art does not provide an activated carbon additive and a preparation process thereof for single-atom lead anchoring for lead-carbon battery negative electrode with more cycle times and higher capacity. Summary of the invention
[0009] In view of this, in order to solve the problems existing in the above-mentioned prior art, the purpose of the present invention is to provide a single-atom lead-anchored activated carbon and its preparation method, related products and applications.
[0010] To achieve the above-mentioned object of the invention, on the one hand, the present invention provides a method for preparing single-atom lead-anchored activated carbon, comprising the following steps: S1. Mix the lead salt and the disodium ethylenediaminetetraacetic acid aqueous solution, add activated carbon, stir, filter, and redisperse in water to obtain a precursor solution; S2, spray pyrolysis of the precursor solution obtained in step S1, cooling, and obtaining single-atom-anchored activated carbon; Wherein, in step S2, the temperature of the spray pyrolysis is 400-800°C, and the spray pyrolysis uses a carrier gas to carry the precursor solution for atomization and pyrolysis.
[0011] Preferably, in step S1, the lead salt is selected from at least one of lead acetate and lead nitrate, the concentration of the disodium ethylenediaminetetraacetic acid aqueous solution is 0.05-2 mol / L, and the molar ratio of the lead salt to the disodium ethylenediaminetetraacetic acid is 1:1-10.
[0012] Preferably, in step S2, the carrier gas is nitrogen or argon, and the ratio of the volume flow rate of the atomized precursor solution to the flow rate of the carrier gas is 1:5-15.
[0013] On the other hand, the present invention provides single-atom lead-anchored activated carbon prepared by the above-mentioned preparation method.
[0014] On the other hand, the present invention provides a carbon additive, comprising the following raw materials in parts by mass: 60-100 parts of activated carbon anchored by monatomic lead, 4-6 parts of acetylene black, 8-12 parts of humic acid, 9-18 parts of barium sulfate, and 8-12 parts of sodium lignin sulfonate; more preferably 80 parts of activated carbon anchored by monatomic lead, 5 parts of acetylene black, 10 parts of humic acid, 10 parts of barium sulfate and 10 parts of sodium lignin sulfonate.
[0015] Wherein, the single-atom lead-anchored activated carbon is the single-atom lead-anchored activated carbon prepared by the above-mentioned preparation method.
[0016] In another aspect, the present invention provides a method for preparing the above-mentioned carbon additive, comprising the following steps: The carbon additive is obtained by mixing the formulated amount of acetylene black, humic acid, barium sulfate, sodium lignin sulfonate and water, adding activated carbon anchored by single atomic lead, atomizing and drying.
[0017] Preferably, the atomization speed of the atomized dried suspension is 0.05-0.5 L / min.
[0018] In another aspect, the present invention provides a lead paste for negative electrode of a lead-carbon battery, comprising the following raw materials by mass: 100-120 parts of lead powder, 0.5-4 parts of carbon additive, 10-13 parts of water and 8-10 parts of aqueous sulfuric acid solution; The carbon additive is the above-mentioned single-atom lead-anchored activated carbon or the above-mentioned carbon additive or the carbon additive prepared by the above-mentioned preparation method.
[0019] On the other hand, the present invention provides the use of the above-mentioned single-atom lead-anchored activated carbon, the above-mentioned carbon additive and / or the above-mentioned lead-carbon battery negative electrode lead paste in a lead-carbon battery.
[0020] In the last aspect, the present invention provides a lead-carbon battery, wherein the negative electrode of the lead-carbon battery contains the above-mentioned single-atom lead-anchored activated carbon, the above-mentioned carbon additive and / or the above-mentioned lead-carbon battery negative electrode lead paste.
[0021] Compared with the prior art, the present invention has the following beneficial effects: The present invention provides a method for preparing single-atom lead-anchored activated carbon, which rapidly prepares single-atom distributed lead-anchored activated carbon materials. The single-atom lead-anchored activated carbon materials are applied to carbon additives and lead pastes for negative electrodes of lead-carbon batteries, effectively improving the number of cycles and capacity of lead-carbon batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is a high-angle annular dark field scanning transmission electron microscopy (HAADF-STEM) photograph of the single-atom lead-anchored activated carbon prepared in Example 1. DETAILED DESCRIPTION
[0023] Terms and Claims of the Present Invention: 1. The articles “a”, “an” and “the” include plural referents unless expressly limited to one or more referents otherwise.
[0024] 2. Numerical range: Unless otherwise expressly stated, all ranges or ratios disclosed herein will be understood to include any and all sub-ranges or sub-ratios contained therein. For example, a range or ratio of 1 to 30 stated should be considered to be included between a minimum value of 1 and a maximum value of 30, and any sub-range or sub-ratio, integer, decimal, or sub-range or sub-ratio consisting of integers or decimals including the end points.
[0025] The following non-limiting examples can enable those skilled in the art to more fully understand the present invention, but do not limit the present invention in any way. The following content is merely an exemplary description of the scope of the present invention, and those skilled in the art can make various changes and modifications to the present invention based on the disclosed content, which should also fall within the scope of the present invention.
[0026] The present invention is further described below by way of specific examples. The various chemical reagents used in the examples of the present invention are obtained through conventional commercial channels unless otherwise specified. Unless otherwise specified, the contents described below are all weight contents. Unless otherwise specified, it is understood that the process is carried out at room temperature.
[0027] Example 1 A method for preparing single-atom lead-anchored activated carbon.
[0028] S1. Mix 30 g (about 90.6 mmol) of lead nitrate with 2 L of 0.1 mol / L disodium ethylenediaminetetraacetic acid aqueous solution, add 100 g of activated carbon, stir for 24 h, filter, and dry at 105 ° C. Redisperse in 2 L of deionized water to obtain a precursor solution.
[0029] S2. Preheat the spray pyrolyzer and control it at 800°C. Use nitrogen to carry the precursor solution and spray the precursor solution into the spray pyrolyzer in an atomized manner. The nitrogen flow rate is 5L / min and the atomization rate of the precursor solution is 0.5L / min. The precursor solution is kept in a stirring state during the atomization spraying process. After spray pyrolysis, the exhaust gas enters the heat exchanger for cooling along with the product. The inlet temperature of the cooling water of the heat exchanger is 25°C and the flow rate is 10L / min. After cooling, single-atom lead-anchored activated carbon is obtained. The yield of the obtained single-atom lead-anchored activated carbon is 109g.
[0030] Example 2 Compared with Example 1, the difference is that in step S1, the amount of lead nitrate is changed to 15 g (about 45.3 mmol), and the rest is the same.
[0031] Example 3 Compared with Example 1, the difference is that in step S1, the amount of lead nitrate used is changed to 66.242 g (about 200 mmol), and the rest is the same.
[0032] Example 4 Compared with Example 1, the difference is that in step S1, the concentration of the disodium ethylenediaminetetraacetic acid aqueous solution is changed to 0.2 mol / L, and the rest is the same.
[0033] Example 5 Compared with Example 1, the difference is that in step S1, the concentration of the disodium ethylenediaminetetraacetic acid aqueous solution is changed to 0.05 mol / L, and the rest is the same.
[0034] Example 6 Compared with Example 1, the difference is that in step S1, the amount of lead nitrate is changed to 132.484 g (about 400 mmol), the concentration of the disodium ethylenediaminetetraacetic acid aqueous solution is changed to 2 mol / L, and the rest are the same.
[0035] Example 7 Compared with Example 1, the difference is that in step S2, the temperature of the spray pyrolyzer is changed to 700° C., and the rest are the same.
[0036] Example 8 Compared with Example 1, the difference is that in step S2, the temperature of the spray pyrolyzer is changed to 600° C., and the rest are the same.
[0037] Example 9 Compared with Example 1, the difference is that in step S2, the temperature of the spray pyrolyzer is changed to 500° C., and the rest are the same.
[0038] Example 10 Compared with Example 1, the difference is that in step S2, the temperature of the spray pyrolyzer is changed to 400° C., and the rest are the same.
[0039] Embodiment 11 Compared with Example 1, the difference is that in step S2, the atomization speed of the precursor solution is changed to 1 L / min, and the rest is the same.
[0040] Example 12 Compared with Example 1, the difference is that in step S2, the atomization speed of the precursor solution is changed to 0.33 L / min, and the rest is the same.
[0041] Comparative Example 1 Compared with Example 1, the difference is that step S1 is replaced by: dispersing 100g of activated carbon in 2L of deionized water, and the other steps are the same. Step S2 is cooled to obtain activated carbon treated by spray pyrolysis.
[0042] Example 13 A method for preparing a carbon additive.
[0043] T1. Evenly mix 5 g of acetylene black, 10 g of humic acid, 10 g of barium sulfate and 10 g of sodium lignin sulfonate with 1 L of deionized water to obtain an additive suspension.
[0044] T2. Take the single-atom lead-anchored activated carbon or the activated carbon treated by spray pyrolysis provided in Example 1 to Example 12 and Comparative Example 1, mix it with the additive suspension synthesized in step T1, and then perform atomization drying to obtain a carbon additive.
[0045] In the actual production process, the synthesized single-atom lead-anchored activated carbon can be added to the additive suspension and mixed before spraying. A better way is to directly spray-dry the single-atom lead-anchored activated carbon obtained by spray pyrolysis together with the tail gas and the atomized droplets of the additive suspension obtained in step T1, and the atomization rate of the suspension is 0.25L / min. The carbon additives obtained in Examples 1 to 12 and Comparative Example 1 using this method are respectively recorded as Ce1-Ce12 and Cc1.
[0046] Comparative Example 2 A method for preparing a carbon additive. The difference from Examples 1 to 12 is that the activated carbon is not synthesized by spray pyrolysis. The specific preparation method is as follows: T1. Evenly mix 5 g of acetylene black, 10 g of humic acid, 10 g of barium sulfate and 10 g of sodium lignin sulfonate with 1 L of deionized water to obtain an additive suspension.
[0047] T2. Mix 30 g (about 90.6 mmol) of lead nitrate with 2 L of 0.1 mol / L disodium ethylenediaminetetraacetic acid aqueous solution, add 100 g of activated carbon, stir for 24 h, filter, dry at 105 °C, place in a tubular furnace, heat at 800 °C for 1 h under a nitrogen atmosphere, cool to room temperature with the furnace, ball mill, and pass through a 200-mesh sieve to obtain lead-modified activated carbon.
[0048] T3. The additive suspension obtained in step T1 and the lead-modified activated carbon (40 g) obtained in step T2 are evenly mixed, and spray-dried under stirring at a suspension atomization rate of 0.25 L / min to obtain a carbon additive, which is recorded as Cc2.
[0049] Embodiment 14 A method for preparing a carbon additive.
[0050] T1. Evenly mix 5 g of acetylene black, 10 g of humic acid, 10 g of barium sulfate and 10 g of sodium lignin sulfonate with 1 L of deionized water to obtain an additive suspension.
[0051] T2. The activated carbon anchored with single-atom lead obtained in Example 1 is mixed with the tail gas and the atomized droplets of the additive suspension obtained in step T1 and spray-dried. The atomization rate of the suspension is 0.05 L / min. The obtained carbon additive is recorded as Ce14.
[0052] Embodiment 15 A method for preparing a carbon additive.
[0053] Compared with Example 14, the only difference is that in step T2, the atomization speed of the suspension is 0.5 L / min, and the rest are the same. The obtained carbon additive is recorded as Ce15.
[0054] Example 16 A method for preparing a carbon additive.
[0055] Compared with Example 14, the only difference is that in step T1, the amount of each raw material is changed to the following: 4g acetylene black, 8g humic acid, 16g barium sulfate and 8g sodium lignin sulfonate; in step T2, the atomization speed of the suspension is 0.25L / min.
[0056] The rest are the same. The obtained carbon additive is recorded as Ce16.
[0057] Embodiment 17 A method for preparing a carbon additive.
[0058] Compared with Example 14, the only difference is that in step T1, the amount of each raw material is changed to the following: 6 g acetylene black, 12 g humic acid, 18 g barium sulfate and 12 g sodium lignin sulfonate.
[0059] The rest are the same. The obtained carbon additive is recorded as Ce17.
[0060] Embodiment 18 A method for preparing lead paste.
[0061] 100 g of lead powder and 2.7 g of carbon additive were put into a paste making machine and mixed for 5 min. 11.5 g of deionized water and 8.8 g of 1.4 g / mL sulfuric acid aqueous solution were slowly added in sequence while stirring to obtain a lead paste.
[0062] Wherein, the carbon additives are selected from Ce1-Ce12, Ce14-Ce17 and Cc1-Cc2 in sequence, and the lead pastes prepared by the above method are respectively recorded as Le1-Le12, Le14-Le17 and Lc1-Lc2.
[0063] Comparative Example 3 A method for preparing lead paste.
[0064] Take 100g lead powder, 0.1g acetylene black, 0.2g humic acid, 0.2g barium sulfate, 0.2g sodium lignin sulfonate and 2g activated carbon, put them into a paste mixer and mix for 5min. While keeping stirring, slowly add 11.5g deionized water and 8.8g 1.4g / mL sulfuric acid aqueous solution in sequence to obtain lead paste (recorded as Lc3).
[0065] Effect evaluation 1. High rate cycle life test.
[0066] 1g of lead paste was applied to the lead alloy grid, and then cured for 24 hours at 50℃ and 90% humidity, and then cured for 12 hours at 60℃ and 80% humidity, and then cooled to room temperature. Take one of the obtained negative plates and two positive plates (purchased from Fujian Huaxu New Energy Battery Co., Ltd., item number NT1.3) and assemble them into a simulated lead-carbon battery according to the battery standard, and package them after formation. The above-mentioned simulated lead-carbon battery was discharged to 50% charge state at 1C current, charged at 2C rate for 60s, left to stand for 20s, and discharged at 2C rate for 60s, and the number of cycle charge and discharge was detected.
[0067] Lead pastes Le1-Le12, Le14-Le17 and Lc1-Lc3 were respectively used to form lead-carbon batteries according to the above method, and the number of cycle charge and discharge was tested. The technical effect of the number of charge and discharge is shown in Table 1: Table 1
[0068] 2. Rate discharge capacity detection.
[0069] Detection method: The rate capacity test is used to analyze the capacity characteristics of the battery at different discharge rates. After full charge, discharge according to the following currents (12.5mA, 25mA, 50mA, 100mA, 12.5mA) and record the discharge capacity, and each current is cycled 5 times. The battery is charged in constant current-constant voltage mode, with the limiting voltage and limiting current being 2.35V and 10mA respectively, and the cut-off current being 3mA. The hour rate capacity is fitted using the Peukert formula.
[0070] The test results are shown in Table 2: Table 2
[0071] 3. Characterization of single-atom lead-anchored activated carbon 3.1 Structural Characterization The single-atom lead-anchored activated carbon prepared in Example 1 was characterized by preparing a sample of the single-atom lead-anchored activated carbon and characterizing it using a high-angle annular dark field scanning transmission electron microscope (HAADF-STEM). Figure 1 shown. Figure 1 In the figure, it can be seen that single atomic lead is distributed throughout the activated carbon material, that is, single atomic lead anchored activated carbon was successfully prepared.
[0072] 3.2. Characterization of lead loading The lead loading of the single-atom lead-anchored activated carbon prepared in Examples 1-12 was characterized by ICP-OES.
[0073] Lead loading = the mass of lead in the monoatom-anchored activated carbon ÷ the total mass of the monoatom-anchored activated carbon × 100%.
[0074] The experimental results are shown in Table 3: Table 3
[0075] It can be seen that the lead content in the carbon additive can be effectively adjusted by the preparation method provided by the present invention.
[0076] Finally, it should be noted that the above content is only used to illustrate the technical solution of the present invention, rather than to limit the scope of protection of the present invention. Simple modifications or equivalent substitutions of the technical solution of the present invention by ordinary technicians in this field do not deviate from the essence and scope of the technical solution of the present invention.
Claims
1. A method for preparing single-atom lead-anchored activated carbon, characterized in that: The following steps are involved: S1. Mix the lead salt and the disodium ethylenediaminetetraacetic acid aqueous solution, add activated carbon, stir, filter, and redisperse in water to obtain a precursor solution; S2. The precursor solution obtained in step S1 is subjected to spray pyrolysis and cooled to obtain single-atom anchored activated carbon; wherein, in step S2, the temperature of the spray pyrolysis is 400-800° C., and the spray pyrolysis uses a carrier gas to carry the precursor solution to atomize and pyrolyze.
2. The preparation method according to claim 1, characterized in that: In step S1, the lead salt is selected from at least one of lead acetate and lead nitrate, the concentration of the disodium ethylenediaminetetraacetic acid aqueous solution is 0.05-2 mol / L, and the molar ratio of the lead salt to the disodium ethylenediaminetetraacetic acid is 1:1-10.
3. The preparation method according to claim 1, characterized in that: In step S2, the carrier gas is nitrogen or argon, and the ratio of the volume flow rate of the atomized precursor solution to the flow rate of the carrier gas is 1:5-15.
4. Single-atom lead-anchored activated carbon obtained by the preparation method described in any one of claims 1 to 3.
5. A carbon additive, characterized in that The method comprises the following raw materials in parts by mass: 60-100 parts of monatomic lead anchored activated carbon, 4-6 parts of acetylene black, 8-12 parts of humic acid, 9-18 parts of barium sulfate and 8-12 parts of sodium lignin sulfonate; wherein the monatomic lead anchored activated carbon is the monatomic lead anchored activated carbon obtained by the preparation method according to any one of claims 1 to 3.
6. The method for preparing the carbon additive according to claim 5, characterized in that: The method comprises the following steps: mixing a prescribed amount of acetylene black, humic acid, barium sulfate, sodium lignin sulfonate and water, adding activated carbon anchored by single-atom lead, atomizing and drying, and obtaining a carbon additive.
7. The preparation method according to claim 6, characterized in that: The atomization speed of the atomized dried suspension is 0.05-0.5 L / min.
8. A lead paste for negative electrode of a lead-carbon battery, characterized in that: The raw materials include the following by mass: 100-120 parts of lead powder, 0.5-4 parts of carbon additive, 10-13 parts of deionized water and 8-10 parts of dilute sulfuric acid; Wherein, the carbon additive is the single-atom lead-anchored activated carbon described in claim 4 or the carbon additive described in claim 5 or the carbon additive prepared by the preparation method described in any one of claims 6-7.
9. Use of the single-atom lead-anchored activated carbon obtained by the preparation method described in any one of claims 1 to 3, the carbon additive described in claim 5, the carbon additive obtained by the preparation method described in any one of claims 6 to 7, or the lead-carbon battery negative electrode lead paste described in claim 8 in lead-carbon batteries.
10. A lead-carbon battery, characterized in that: The negative electrode of the lead-carbon battery contains the activated carbon anchored by single-atom lead obtained by the preparation method described in any one of claims 1 to 3, or the carbon additive described in claim 5, or the carbon additive obtained by the preparation method described in any one of claims 6 to 7, or the lead paste for the negative electrode of the lead-carbon battery described in claim 8.
Citation Information
Patent Citations
Preparation method of carbon-based additive used for lead-carbon negative electrode
CN107742696A
Lead-charcoal composite material, as well as preparation method and application thereof
CN108899492A
Additive-loaded activated carbon composite material as well as preparation and application thereof
CN114497544A